Need of the hour: Student-centered Learning in undergraduate Medical Curriculum - Kainat Javed, Ahmad Naeem Akhtar, Umair Bin Nasir, Nazia Farooq, Shehroze Sikandar, Muhammad Rizwan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Student-centered learning is becoming more prevalent in medical education, especially during large-group lectures. The variety and abundance of active learning techniques used in first-year MBBS large group format were investigated. Aim: To investigate the relationships between student-centered learning and the characteristics and distribution of student-centered teaching approaches in large group settings. Methods: This was a descriptive exploratory study in which by means of purposive sampling 25 faculty members who were involved in teaching in large and small groups were identified, out of these 25 faculty members, 15 members were chosen for interviews by convenient sampling. Retrospective curriculum evaluations and semi-structured interviews were used to collect the data. The authors tested a taxonomy of student-centered learning strategies and linked those strategies to the characteristics of education. Results: Over the course of six modules in the first year, teachers used 13 different strategies for active learning. 996 out of 1190 hours of large group teaching included a minimum of one active learning element. 83% of the curriculum's hours in the first year of MBBS had an active learning component. Practical implications: Many small group-learning approaches are included in active learning, and they may help undergraduate students achieve a higher level of cognitive skills through group engagement. Different kinds of small-group learning have been shown to be successful in fostering higher academic accomplishment, more positive attitudes toward learning, and enhanced persistence. Conclusions: The frequency and diversity of active learning elements incorporated into the first-year MBBS curriculum show how acquainted faculty are with these techniques and how supportive they are of interactive teaching culture. This research has stimulated discussion about instructional strategies and aided the transition from teacher-centered to learner-centered teaching. Keywords: Student-centered learning, active learning, interactive studies, critical thinking, game-based.